2018
DOI: 10.1016/j.jmoldx.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Gene Fusions in Bone and Soft Tissue Tumors by Anchored Multiplex PCR–Based Targeted Next-Generation Sequencing

Abstract: Molecular assays for translocation detection in bone and soft tissue tumors have gradually been incorporated into routine diagnostics. However, conventional methods such as fluorescence in situ hybridization (FISH) and reverse transcriptase-PCR come with several drawbacks. In this study, the applicability of a novel technique termed anchored multiplex PCR (AMP) for next-generation sequencing (NGS), using the Archer FusionPlex Sarcoma kit, aimed at 26 genes, was evaluated and compared with FISH and reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 23 publications
3
63
0
Order By: Relevance
“…AMP-based NGS has been already used by other authors [16] to reveal the presence or absence of gene fusion in the background of unusual signals during FISH testing of ALK and ROS1. The method allows detection of ALK gene rearrangements even without prior knowledge of the partner gene [17,18]. As both new and known fusion variants can be detected with AMP, ambiguously positive FISH cases can be sorted out confidently in this way.…”
Section: Discussionmentioning
confidence: 99%
“…AMP-based NGS has been already used by other authors [16] to reveal the presence or absence of gene fusion in the background of unusual signals during FISH testing of ALK and ROS1. The method allows detection of ALK gene rearrangements even without prior knowledge of the partner gene [17,18]. As both new and known fusion variants can be detected with AMP, ambiguously positive FISH cases can be sorted out confidently in this way.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported a slightly lower concordance using the Archer FusionPlex kit compared with pre‐existing techniques; however, this was a larger series that tested a greater diversity of fusions genes—and it is worth noting that most of their discrepancies were reconciled by independent testing that ultimately demonstrated the NGS technique was superior to conventional FISH and RT‐PCR . The authors of this study reported an overall failure rate of 14% with the Archer FusionPlex kit; this was attributed to both decalcification and heterogeneity in tissue and fixation conditions . In our hands, likewise using FusionPlex, we encountered a fairly similar percentage of test failures when evaluating this platform for possible implementation, especially with samples demonstrating poor quality RNA.…”
Section: Introductionmentioning
confidence: 54%
“…23 The authors of this study reported an overall failure rate of 14% with the Archer FusionPlex kit; this was attributed to both decalcification and heterogeneity in tissue and fixation conditions. 23 In our hands, likewise using FusionPlex, we encoun-…”
Section: 31 | Selection Of An Assaymentioning
confidence: 82%
See 1 more Smart Citation
“…This translated into more accurate classification and also prognostication of soft tissue tumors . At present, the two novel molecular multiplex methods commonly used in Dutch sarcoma centers are the anchored multiplex PCR (AMP)‐based NGS (Archer FusionPlex Sarcoma assay) and the NanoString nCounter platform . The Archer AMP PCR method targets exons of 26 genes commonly involved in fusion genes of soft tissue tumors, whereas the NanoString assay is a high‐throughput hybridization technique, which uses specific probes that target 174 unique gene fusion junctions in 22 soft tissue tumor types …”
Section: Introductionmentioning
confidence: 99%